2022
DOI: 10.1387/ijdb.210180gk
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-to-mesenchymal transition of tumor cells: cancer progression and metastasis

Abstract: Detection and characterization of circulating tumor cells (CTCs) with an epithelial-to-mesenchymal transition (EMT) phenotype is very important as it can contribute to the identification of high-risk for relapse and death patients. However, most of the methods are underestimating CTC numbers, due to their dependence on epithelial markers. In the current study, we evaluated the EMT phenotype in CTCs isolated from breast cancer (BC) patients, using the CellSearch system. Spiking experiments for the evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…More specifically, gene and protein expression of both markers was markedly reduced in DU-145 with KDM2B overexpression ( Zacharopoulou et al, 2018a ). We have also shown that EMT phenotypes are upregulated in CTCs, promoting their migration into the bloodstream ( Kallergi et al, 2011 , Pantazaka et al, 2021 , Vardas et al, 2022 ). KDM2B is involved in various signaling pathways crucial in tumorigenesis ( Yan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 83%
“…More specifically, gene and protein expression of both markers was markedly reduced in DU-145 with KDM2B overexpression ( Zacharopoulou et al, 2018a ). We have also shown that EMT phenotypes are upregulated in CTCs, promoting their migration into the bloodstream ( Kallergi et al, 2011 , Pantazaka et al, 2021 , Vardas et al, 2022 ). KDM2B is involved in various signaling pathways crucial in tumorigenesis ( Yan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 83%
“…Proteomics related research reported that vimentin is a metastasis related factor of various malignant tumors, such as prostate cancer and breast cancer, which indicates that it may play an important role in tumor progression and become a potential biomarker of metastasis ( 31 ). ZEB1, a master regulator of the EMT, which regulates the expression of vimentin ( 32 ), has been reported to facilitate tumor invasion and metastasis by inducing EMT in various tumors. ZEB1 belongs to the E-box binding zinc finger protein family and promotes downstream gene transcription by binding to E-box promoter elements ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intravasation of CTCs via EMT after active crossing of tumor stroma is expected to result in fully viable and not apoptotic cells. Marker-independent CTC enrichment techniques demonstrate a variety of CTC EMT partial phenotypes with minor upregulation in vimentin and downregulation in E-cadherin without a true cell-type transformation ( 82 , 83 ). Furthermore, the number of CTCs that have intravasated seems to be correlated to the microvessel density of the tumor but not to the tumor mass.…”
Section: Mechanisms Of the Intravasation Of Ctcsmentioning
confidence: 99%